DISPARITAS PENJATUHAN HUKUMAN PIDANA DALAM PERKARA KEKERASAN FISIK DALAM RUMAH TANGGA YANG DILAKUKAN SUAMI TERHADAP ISTRI DI PENGADILAN NEGERI JAMBI - Suzanalisa Suzanalisa (Universitas Batanghari Jambi, 2017)
This study aims to determine and analyze the effectiveness of Law Number 23 Year 2004 in the settlement of cases of domestic violence in the jurisdiction of Jambi City and explain the concept of reform Law No. 23 of 2004 in solving cases of domestic violence in the jurisdiction of the city of Jambi. This research uses